Molecular detection of virulence genes in pseudomonas aeruginosa isolated from different clinical infections - Enass Abdul Kadhum Almkhadhree; Kawther Adnan Alqaseer; Khairi Jameel AL Ruaby (Journal of the Pakistan Medical Association, 2023)
Objective: To isolate pseudomonas aeruginosa from different clinical specimens, and to detect virulence factors. Method: The cross-sectional study was conducted at Al-Zharr Hospital and private clinics in Kut city of Wasit province in Iraq from October 15, 2021, to April 30, 2022, and comprised samples obtained from different patient sites, such as wound swabs, ear swabs, urine samples, burn swabs and respiratory tract swabs. The samples were subjected to molecular testing using, among other tools, polymerase chain reaction. The isolates were cultured on different media, such as blood agar, MacConkey agar and cetrimide agar, and were further diagnosed by biochemical testing. Data was analysed using SPSS 20. Results:Of the 212 samples, there were 70(33%) wound swabs, 53(25%) ear swabs, 41(19.3%) urine samples, 33(15.6%) burn swabs and 15(7%) respiratory tract swabs. Pseudomonas aeruginosa was identified in 54(25.47%) isolates via culture-based characterisation. All 54(100%) isolates were positive for mexR and toxA on polymerase chain reaction, 44(81.48%) were positive for exoU gene, 43(79.62%) for exoT gene, 36 (66.66) for exoT gen, 35(64.81%) for plcH, gene and 14(25.92 %) for exoS gene. Conclusions: Wound swabs were found to be the most common site for pseudomonas aeruginosa, followed by ear swabs and urine samples. Keywords: Pseudomonas aeruginosa, Virulence, Agar, Cetrimonium, Virulence, Burns, Polymerase chain reaction, DNA.